2021
DOI: 10.21203/rs.3.rs-566699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping of Potential Groundwater Recharge Zones: A Case Study of Maputaland Coastal Plain, South Africa

Abstract: The potential groundwater zones of the Maputaland coastal plain of Kwazulu-Natal is identified by comparing the Analytic hierarchy process (AHP)-Multi criteria decision-making (MCDM)techniqueand Boolean logical approach. The map of groundwater potential zones was prepared by generation and integration of 8 thematic layers, i.e. geology, geomorphology, lineament density, soils, slope, rainfall and land use. Each thematic layer wereassigned with subjective relative weights under AHP-MCDM technique and Boolean lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Water scarcity has been identified as a major issue, especially in developing nations where there are insufficient exploration methods and inadequate water supply to meet the population demand [1]. South Africa has recorded inadequate water distribution with a sharp increase in water shortage [2], where provinces such as Eastern Cape have declared a surge in water demand since municipalities were confronted with the challenge of meeting water users' demands. Since surface water faces many challenges, including availability, scientists have revealed that groundwater could play a significant role in meeting water users' demands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water scarcity has been identified as a major issue, especially in developing nations where there are insufficient exploration methods and inadequate water supply to meet the population demand [1]. South Africa has recorded inadequate water distribution with a sharp increase in water shortage [2], where provinces such as Eastern Cape have declared a surge in water demand since municipalities were confronted with the challenge of meeting water users' demands. Since surface water faces many challenges, including availability, scientists have revealed that groundwater could play a significant role in meeting water users' demands.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, they assist in explaining features that could be associated with the availability of groundwater [16]. The GIS approach has been integrated with various techniques, such as multicriteria decision-making methods including analytical hierarchical process (AHP) which is widely used for groundwater mapping [2,5,8,17], and fuzzy-AHP [18,19], multi-influencing factor (MIF), fuzzy logic (FL), certainty factor (CF) [20], weight of evidence (WOE) [21], evidence belief function (EBF) [22] for landslide mapping, and index models (IMs) [17,23]. Other researchers, such as Mogaji et al [24], have also attempted to delineate GWPZs based on techniques such as the Dempster-Shafer theory of evidence (DS-EBF) model, which revealed great accuracy.…”
Section: Introductionmentioning
confidence: 99%